"Don't pack a pest": parts, wholes, and the porosity of food borders. (20th October 2019) - Paxson, Heather
ABSTRACT: Food retailers, restaurateurs and transnational families rely on continual border-crossings for the global circulation of foodstuffs. Those crossings are highly regulated. Not everything gets in. This paper provides an overview of how food safety is (unevenly) enacted at U.S. ports of entry. Where government regulators and enforcement agents perceive in certain foods danger of adulteration or contamination, importers and producers also experience threat to customary practices of foodmaking, provisioning and commerce. Synecdochic, part-for-whole, reasoning guides food journeys and helps determine the fate of perishable foods as they attempt to cross semi-permeable thresholds that delineate and connect nation-states, and that make possible, even as they also restrict, the flow of international trade.